A Review of Water Pollution in the Israel-Palestinian Conflict Region - Nica, Miruna-Amalia; Costache, Mihnea-Stefan; Marin, Maria-Ioana; Manoiu, Valentina-Mariana (European Scientific Journal, ESJ, 2024)
Water pollution is a daily risk with a major impact on both populations and ecosystems. An analysis of water pollution types is essential to determine the affected regions and the magnitude of its impact on various components of the geosystem. This study aims to conduct a thorough analysis of water pollution in the Israel-Palestine conflict region, focusing on the three main types of pollution: physical, chemical, and biological. The methodology of this article is based on the critical review of 22 scientific papers published between 1972 and 2023, addressing various aspects of water pollution in the analyzed region, from generating sources to their impact. Most studies are authored by researchers affiliated with institutions located in the conflict region, with many samples collected directly from the field and processed in laboratories or GIS environments. The study results highlight chemical pollution often exceeding recommended limits for various analyzed parameters. Biological pollution subjects aquatic ecosystems to significant pressures, including eutrophication and harmful algal blooms. Wastewater is discharged into watercourses in the region, affecting their physical properties. Areas subject to water pollution include the Gaza Strip, the coastal zone, the northern aquifer in Israel, and lakes in the western part of the analysis region, posing potential risks to the health of the populations in Israel and Palestine.